PENINGKATAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DIRECT INSTRUCTION DI KELAS XI SMK MUHAMMADIYAH TEGAL - Awik Suharyanto (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to improve mathematics learning outcomes using the direct learning model of grade XI students of SMK Muhammadiyah Tegal for the 2022/2023 academic year. The research method used in this study is Classroom Action Research (PTK) This research was conducted in two cycles, the sample in this study was grade XI students of SMK Muhammadiyah Tegal. The results of the research obtained in this study were the average student learning outcomes in the pre-cycle was 58.24 then in the first cycle the average acquisition of student learning outcomes was 65.59 with classical learning completeness of 35.29%, in the second cycle the average acquisition of learning outcomes was 75 with classical learning completeness of 82.36%. Based on the results of this study, it can be concluded that the direct learning model can improve students' mathematics learning outcomes.